PENYULUHAN KELUARGA BERENCANA ( KB) PADA DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3P2&KB) KOTA PADANG - Rini Parmila Yanti; Zulkarnaen Zulkarnaen (Jurnal Public Administration, Business and Rural Develoment Planning, 2019)
From the objectives of the research carried out, namely: 1. To find out family planning counseling at the Office of Women's Empowerment of Child Protection for Population Control and Family Planning (DP3AP2 & KB) Kota Padang 2. To find out the factors that influence the implementation of counseling. Family Planning By the Office of Women's Empowerment of Child Protection Population Control and Family Planning (DP3AP2 & KB) Padang City. This study uses descriptive method with a qualitative approach. From the results of the research and discussion, the following conclusions and suggestions were obtained: 1. Family planning counseling at the Office of Women's Empowerment of Padang Population Control and Family Planning (DP3AP2 & KB) "is a process of delivering information to change behavior through non-formal education. Such behavior changes are not necessarily due to counseling but are influenced by other factors. 2 Factors that influence the implementation of such counseling include the level of education, the level of socio- economic, traditional customs, public trust and the availability of time to attend an extension program. From the above conclusions, it is suggested the following: 1. It is expected that extension agents at DP3AP2 & KB Kota Padang can prepare themselves before going down to the field because there are still many target groups that differ in education and economic background2. For successful extension, it is necessary to coordinate with other agencies that have the same extension program.